(untitled) (Journal of Economics and Sustainability, 2021)
There exists a potential decline in tax revenue to government among firms with foreign involvement. The main aim of the study is to examine the impact of foreign involvement on corporate tax noncompliance. The study focuses on the effects of foreign CEO, the percentage of foreign executive board members, and the ratio of stocks owned by foreign directors on corporate tax noncompliance. Data on manufacturing firms were utilized based on data availability from 2015 to 2019. Generally accepted accounting principle effective tax rate was utilized as a primary measure of tax noncompliance and fixed effect technique of regression analysis. Controlling for profitability, leverage, firm size and board size, the findings of the study revealed a significant negative effect of the percentage of foreign executives’ shareholding on GAAP ETR. Our result is robust to using cash effective tax rate as an alternative proxy for tax noncompliance. The implication of this finding is that an increase in foreign executive shares will reduce tax proceeds. Given the corporate tax implication, regulatory authorities should weigh the cost and benefit of a benchmark for foreign directors’ equity ownership. Received 8 May 20. Revised 6 September 20. Accepted 17 September 20.